Parental Education and Children’s Sleep Problems: Minorities’ Diminished Returns - Shervin Assari (International Journal of Epidemiologic Research, 2021)
Background and aims: While increased parental education reduces children’s sleep problems, less is known about racial variation in such protection. According to Minorities’ Diminished Returns (MDRs) theory, economic resources such as parental education show weaker health effects for minority groups such as Blacks and Latinos than non-Latino Whites, which is due to racism and social stratification. In this study, we investigated the association between parental education and children’s sleep problems, as a proxy of sleep problems, by race.   Methods: This cross-sectional study included 11718 American children aged 9-10. All participants were recruited to the Adolescent Brain Cognitive Development (ABCD) study. The independent variable was parental education, a five-level nominal variable. The dependent variable – sleep problems, was a continuous variable. Race/ethnicity was the effect modifier. Age, sex, and marital status were the covariates. Mixed-effects regression models were used for data analysis.   Results: Parental education was associated with children’s sleep problems. However, there was a weaker inverse association seen in non-Latino Black and Latino families compared to non-Latino White families. This was documented by a significant statistical interaction between race and ethnicity and parental education on children’s sleep problems.   Conclusion: Diminished protective effect of parental education on children’s sleep problems for non- Latino Black and Latino families compared to non-Latino White families is similar to the MDRs in other domains. Worse than expected sleep may contribute to higher-than-expected health risks of middle-class Black and Latino children.